2021
DOI: 10.3389/fphar.2021.678886
|View full text |Cite
|
Sign up to set email alerts
|

Loganin Inhibits Angiotensin II–Induced Cardiac Hypertrophy Through the JAK2/STAT3 and NF-κB Signaling Pathways

Abstract: Loganin is an iridoid glycoside extracted from Cornus officinalis, which is a traditional oriental medicine, and many biological properties of loganin have been reported. Nevertheless, it is not clear whether loganin has therapeutic effect on cardiovascular diseases. Hence, the aim of the present study was to investigate the effect of loganin on Ang II–induced cardiac hypertrophy. In the present study, we reported for the first time that loganin inhibits Ang II–provoked cardiac hypertrophy and cardiac damages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…All cell lines were maintained in a 5% CO 2 humidified cell incubator at 37 °C. The cells were treated with 1 μM angiotensin II (Xu et al, 2021).…”
Section: Cell Culturementioning
confidence: 99%
“…All cell lines were maintained in a 5% CO 2 humidified cell incubator at 37 °C. The cells were treated with 1 μM angiotensin II (Xu et al, 2021).…”
Section: Cell Culturementioning
confidence: 99%
“…Recently, a study highlighted the protective role of Morroniside against H 2 O 2 -induced damage; further studies suggested that treatment with Morroniside decreased apoptosis, autophagy, and oxidative stress in rat ovarian granulosa cells through the PI3K (phosphatidylinositol 3-kinase)/AKT (serine/threonine-specific protein kinase)/mTOR (mechanistic target of rapamycin) pathway [ 15 ]. According to reports, Loganin mitigates Ang II-induced cardiac hypertrophy, at least partially, through inhibiting the JAK 2 (Janus Kinase 2) / STAT 3 (signal transducers and activators of transduction-3) and NF-κB (Nuclear factor-κB) signaling pathways and might be a novel effective agent for the treatment of cardiac hypertrophy and heart failure [ 16 ]. A quantibody array analysis demonstrated that Polygalaxanthone III downregulates inflammation in lipopolysaccharide-stimulated RAW264.7 macrophages [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Loganin, one of the most common iridoid glycosides isolated from Cornus species, was recently investigated on angiotensin II-induced cardiac hypertrophy [193]. Angiotensin II is a significant component of the renin-angiotensin system and plays an important role in triggering hypertension and myocardial hypertrophy.…”
Section: Other Bioactivitiesmentioning
confidence: 99%
“…Inhibition of angiotensin II. Cardioprotective effects through a decrease in pro-inflammatory cytokine secretion, suppression of phosphorylation of critical proteins including STAT3, JAK2, IκBα, and p65, and attenuation of cardiac fibrosis [193][194][195][196][197] Ophthalmic activity…”
Section: Loganinmentioning
confidence: 99%